Significance of Electrocardiographic QTc Interval on Assessment of Left Ventricular Diastolic Dysfunction in Hypertensive Patient: A Simple Screening Tool - Sheila Dhiene Putri; Harris Hasan; Refli Hasan; A. Afif Siregar; Nizam Akbar; Cut Aryfa Andra (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
Background: Diastolic dysfunction as part of heart failure with preserved ejection fraction (HFpEF) has gain interests, due to the increasing prevalence rate and poor prognosis. Besides the mechanism is not fully understood, there are some difficulties in detecting the presence of diastolic dysfunction. Previous studies have shown correlation between some electrocardiographic parameters and diastolic function. Furthermore, the aim of this study is to assess the diagnostic value of the QTc interval in detecting left ventricular diastolic dysfunction.Methods: A cross sectional study was conducted on patients with clinical suspicion of heart failure. Electrocardiographic examination was performed to obtain QTc interval (msec) using the Bazett formula. Left ventricular diastolic function was assessed using Tissue Doppler Imaging by echocardiography. Using correlation test and ROC method, the relationships between QTc interval and LV diastolic function were investigated.Results: Of 82 patients analyzed, there were 62 patients (75.9%) known to have diastolic dysfunction. The QTc interval was found to be longer in the group with diastolic dysfunction compared to the normal group (442.9±27 vs. 402.1±18.2, p <0.001). There was a strong negative correlation between the QTc interval and diastolic function (r = -0.619; p <0.001). Using ROC analysis, the cut off point for QTc interval was 410 ms with 91% sensitivity, 70% specificity, and 90% positive predictive value.Conclusion: The QTc interval is an accurate, simple and highly feasible electrocardiographic parameter as a screening tool to determine the presence of left ventricular diastolic dysfunction.